Enhanced B cell and complement cascade gene signatures in patients with neuropsychiatric systemic lupus erythematosus - Nikolopoulos, Dionysis; Sentis, George; Kitsios, Iasonas; Garantziotis, Panagiotis; Kapsala, Noemin; Pieta, Antigone; Flouda, Sofia; Manolakou, Theodora; Nikoloudaki, Myrto; Banos, Aggelos; Chavatza, Katerina; Parodis, Ioannis; et al. (Annals of the Rheumatic Diseases, 2025)
Objectives: The management of neuropsychiatric systemic lupus erythematosus (NPSLE) remains challenging because of clinical heterogeneity and the complexity of pathophysiologic mechanisms involved. We sought to determine the molecular signature of NPSLE and its endotypes towards novel biomarkers and targeted therapies. Methods: Whole-blood RNA sequencing from 308 patients with systemic lupus erythematosus (119 with NPSLE, 189 non-NPSLE) and 72-matched healthy controls (HCs) were performed. Supervised pathway enrichment analysis and unsupervised weighted gene coexpression network analysis were applied to distinguish clinically and molecularly defined NPSLE endotypes. Results: Compared with HCs, patients with NPSLE demonstrated dysregulation of adaptive immune responses along with upregulation of interleukin (IL)-1, IL-6, IL-17, and IL-12/IL-23 signalling pathways. The comparison between NPSLE and non-NPSLE groups revealed a robust upregulation of complement cascade, DNA damage response, adaptive immunity, and IL-1 and IL-6 signalling. Furthermore, active NPSLE exhibited a strong autophagy signature. The B cell and complement cascade signatures exhibited a gradual upregulation across the non-NPSLE, inactive NPSLE, and active NPSLE subgroups. Within NPSLE, diffuse syndromes correlated positively with the oxidative phosphorylation module, while antiphospholipid antibody–positive NPSLE was not associated with specific signatures by unsupervised analysis. NPSLE endotypes such as cognitive dysfunction, seizures, psychosis, and optic neuritis were associated with distinct transcriptomic signatures namely IL-6 signalling and leukocyte migration, DNA damage response, inflammation, and type-I interferon, respectively. Conclusions: The clinical heterogeneity of NPSLE appears to be associated with molecular diversity, with certain endotypes or syndromes exhibiting distinct gene signatures. Upregulation of adaptive immune response and complement cascade suggests that complement inhibitors and B cell–targeted therapies could be further explored in NPSLE.
CRIS-Team Scopus Importer:2025-05-23